Socio-economic factors affecting growth of micro and small scale manufacturing enterprises: a survey of select firms in the food and beverage industry in Kenya - Mukabana, Floice Okenzo (My University, 2011)
Small and medium enterprises (SMEs) are playing an increasingly important role in the process of economic growth in the developing world. They are the largest group in terms of the number of industrial units in most developing countries and make a significant contribution to manufacturing output and employment. A review of the nature of entrepreneurship indicates that growth and transition into larger enterprises is essentially an entrepreneurial process Education and training is expected to equip the owners/managers to better manage and exploit opportunities for the growth of the enterprise while accessing new markets as well as credit influences profitability and business sustainability. Firm age determines its learning curve and intra firm linkages both vertical and horizontal. Underlying these developmental achievements are SME’s widely held advantages in income growth, entrepreneurial training, creation of technological capabilities, greater flexibility to changing market circumstances, job creation and lower wage inequality and dispersion of industry away from urban areas and regional development. Building on national markets and advantages, SMEs have the potential to become a powerful engine of manufactured export growth and upgrading in the developing world. A he research design adopted in this study was descriptive and qualitative in nature. Tlie sampling design was stratified sampling method. Quantitative data that was used was numerical while qualitative data was non-numerical where as information in the annual reports given was in numerical form. The data obtained was analyzed and the findings presented in the form of frequencies, percentages and picf charts. Key findings of this study established that enterprises do increase their social networks as they age, legal structures of the business on the growth of the enterprises indicated that policy making institutions ignore SMEs. Another key finding in regard to the objectives of this study was that the respondents affirmed they had formal or written business plans prior to starting the business within the SMEs segment. More than half indicated they had difficulties in accessing finances/credit either for ex^ansion_or_start-up both corruption and dysfunctional markets was also highlighted as a hindrance and poor financial management respectively, lack of collateral and poor accounting policies formed a bander in funds acquisitions. However there was growth among the number of employees in 2011 as compared to 2006. This study concluded that in financial markets, improving SMEs access to credits requires an increase in the number of financial institutions that find lending to SMEs to be profitable and therefore sustainable. Easy accessibility to credit through specialized or development oriented banking or financing institutions. Funds being made available through these sources should be given at preferential interest rates. This study confirms that SMEs have adopted a myriad of strategic responses in dealing with changes in the business environment in regard to growth and expansion. Several factors were identified as hindering the practice of strategic marketing. These include; lack of market information on new products, prices, competitors, demand for products and quality, lack of enough capital, lack of product assortment, failure to enter new markets, lack of enough stock, poor bargaining power on prices, high costs of operations among others.. Marketing education should be emphasized among the SMEs through effective market research and appropriate strategic choices.